Effects of a polysaccharide extract from Amomum villosum Lour. on gastric mucosal injury and its potential underlying mechanism. (15th October 2022) - Liu, Huifan; Zhuang, Shanshan; Liang, Churong; He, Junjun; Brennan, Charles Stephen; Brennan, Margert Anne; Ma, Lukai; Xiao, Gengsheng; Chen, Hao; Wan, Shuo
Abstract: AVLP-2, a novel acidic polysaccharide, was isolated and purified from Amomum villosum Lour. The structural characteristics of the polysaccharides were characterized using monosaccharide composition, methylation, FT-IR, and NMR techniques. Results showed that AVLP-2 comprises galactose and glucose monomers, has a molecular weight of 10.488 kDa, and has backbone structures →4)-α-d -GalAp-(1→3, 4)-α-d -GalAp-(1→, →4)-α-d -GalAp-(1→6)-α-d -Galp-(1→, and n→6)-α-d -Galp-(1→4)-β-d -Glcp-(1→, with α-d -Galp-(1→ branches. Furthermore, AVLP-2 had a significant protective effect against oxidative stress in alcohol-induced injury and LPS inflammation models GES-1 cells by regulating the levels of ROS and inflammatory factors. In the animal experiments, AVLP-2 improved the oxidative stress status of the gastric mucosa by increasing SOD activity and GSH levels and inhibiting the excessive generation of malondialdehyde in tissues. The levels of MPO, IL-1β, IL-10, and NF-κB p65 were downregulated, while that of TNF-α was upregulated by AVLP-2 treatment, thereby reducing the alcohol-induced inflammation. Graphical abstract: Unlabelled Image